2014
DOI: 10.1364/ol.39.005594
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of burns in a mouse model using spectroscopic optical coherence tomography

Abstract: Spectroscopic analysis of biological tissues can provide insight into changes in structure and function due to disease or injury. Depth resolved spectroscopic measurements can be implemented for tissue imaging using optical coherence tomography (OCT). Here spectroscopic OCT is applied to in vivo measurement of burn injury in a mouse model. Data processing and analysis methods are compared for their accuracy. Overall accuracy in classifying burned tissue was found to be as high as 91%, producing an area under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 27 publications
2
26
1
Order By: Relevance
“…7(a). The power-law exponents of both the burned and healthy phantom (b = −1.3 and 1.2, respectively) are similar to those reported in earlier studies [19,20], which showed b = −1.4 and 1.8 for burned and healthy tissue when fit across the same bandwidth (770-830 nm) used in this study. Figure 7(b) shows color coded images of layered phantoms in which each pixel in the full cross-sectional image was color coded based on the power-law exponent.…”
Section: supporting
confidence: 88%
See 2 more Smart Citations
“…7(a). The power-law exponents of both the burned and healthy phantom (b = −1.3 and 1.2, respectively) are similar to those reported in earlier studies [19,20], which showed b = −1.4 and 1.8 for burned and healthy tissue when fit across the same bandwidth (770-830 nm) used in this study. Figure 7(b) shows color coded images of layered phantoms in which each pixel in the full cross-sectional image was color coded based on the power-law exponent.…”
Section: supporting
confidence: 88%
“…The color map is designed so that dark red color represents a small power-law exponent, which suggests burned tissue; while a light pink color represents a large power-law exponent suggesting healthy tissue. These images show good spectroscopic contrast between burned and healthy tissue regions and more importantly, they revealed an improved penetration depth of approximately 750 μm, which is much higher than the previously reported depth of ~250 μm for conventional OCT measurements [19,20]. Color coded images of layered phantoms using power-law exponent reveal differences between burned and healthy tissue with a larger lateral scan range and an improved penetration depths compared to [20] (Arrow pointing to tissue phantom interface, scale bars: 250μm).…”
Section: mentioning
confidence: 52%
See 1 more Smart Citation
“…For instance, optical coherence tomography (OCT) can measure depth-resolved tissue morphology up to one millimeter below the tissue surface [3,4] depending upon the type of tissue and its associated optical properties. Chemically-sensitive optical methods, such as Raman spectroscopy (RS) [5][6][7][8][9][10][11], can measure spatiotemporal distributions of analytes with up to micron-level spatial resolution when utilizing confocal detection [12].…”
Section: Introductionmentioning
confidence: 99%
“…In a first step, we analyze ex vivo brain tumor tissue samples. Employing spectroscopic analysis of the OCT data, wavelength dependent depth profiles can be obtained by using a Short Time Fourier Transform (STFT) [8] [9]. The window size has an influence on the Time-Frequency distribution [10].…”
Section: Introductionmentioning
confidence: 99%